Impact of Government Livestock Intervention Programmemes in Ghana: A Perspective - Sumah, M.M.A. (University of Ghana, 2015)
Livestock development projects are aimed at increasing livestock productivity and increasing household incomes of participating livestock farmers and processors and traders in Ghana. Ghana has implemented two of such projects within the last two decades: The “National Livestock Services Project” and “Livestock Development Project”. The components of these projects were development of animal production, development of animal health, credit provision, and capacity building. The credit facility which was short to medium term loan to enable beneficiaries to access feed, drugs and veterinary services, construct storage facility or purchase milk processing equipment was converted to animals for a “credit in kind” due to bottlenecks encountered with the disbursement. The study was conducted to assess the impact of these projects on livestock development and livelihoods of farmers and processors who were the primary beneficiaries of these projects. Data was collected from five participating regions namely Ashanti, Greater Accra, Northern, Upper West and Volta Regions. Information was primarily obtained from semi-structured interviews with 129 livestock farmers and processors as respondents. In terms of the impact of the projects indicated, capacity building was the most dominant. In fact a little over forty-five percent (45.31%) of respondents testified that acquisition of knowledge and skills have helped improved livestock production with a few adopting a more business approach to livestock. Improved knowledge and credit facility assisted some of the farmers to expand their farm enterprises (thirteen percent [13.28%]), while over a third of the respondent (thirty-four percent [33.59%]) increased their incomes either through processing or farming. Among the livestock development activities, breed improvement had the least attention. A change in policy to foster closer collaboration among all stakeholder institutions, farmer involvement in planning, capacity development of project staff, development and implementation of sustainable animal breeding programmes were recommended.
Thesis (MPhil) - University of Ghana, 2015